Medicinal Plants for Chemoradiotherapy-Induced Oral Mucositis: A Review of Clinical Studies - Roodabeh Bahramsoltani (Tehran University of Medical Sciences, 2017)
Oral mucositis is one of the severe complications of chemoradiotherapy in patients with cancer. Current treatments such as artificial saliva, antimicrobial agents, and local analgesics could not fully satisfy patients and thus, further investigations are essential. Medicinal plants, containing a wide variety of phytochemicals may be suitable suggestions to be investigated for the management of this complication in cancer patients. To review current literature regarding the effectiveness of herbal preparations in chemoradiotherapy-induced oral mucositis, electronic databases including PubMed, Scopus, and Cochrane library were searched using "mucositis" or "xerostomia" or "dry mouth" in the title/abstract, and "plant" or "extract" or "herb" or "phytochemical" keywords in the whole text up to August 2017. A total of 14 clinical trials were finally included. Aloe vera (aloe), Matricaria chamomilla (German chamomile), Malva sylvestris (high mallow), and Alcea digitata (hollyhock) are the most evident medicinal plants useful for the management of oral mucositis and xerpstomia. Mucilage, flavonoids, flavonolignans and terpenoids are the active ingredients which show soothing effect on the lesions of oral cavity. Herbal preparations could reduce the duration of ulceration, ulcer severity, pain and use of analgesics, as well as dysphagia and the need for total parenteral nutrition. In conclusion, medicinal plants are capable of improving chemoradiotherapy-induced oral mucositis and xerostomia in patients with cancer. Future well-designed clinical trials are required for further confirmation of the safety and efficacy of medicinal plants for the management of oral mucositis.